2011
DOI: 10.1016/j.atherosclerosis.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Association of gene variants with lipid levels in response to fenofibrate is influenced by metabolic syndrome status

Abstract: Objective Fenofibrate therapy reduces serum triglycerides (TG) and increases high-density lipoprotein-cholesterol (HDL-C) and thus addresses the atherogenic dyslipidemia associated with metabolic syndrome (MetS). Our hypothesis is that genetic factors contribute to the variability of lipid response to fenofibrate differently in subjects with MetS and without MetS. Methods We investigated the association in 25 candidate genes with lipid responses to a 3-weeks trial on fenofibrate in subjects with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(51 reference statements)
0
11
1
1
Order By: Relevance
“…The role of APOA5 alleles had already been widely studied (Szalai et al 2004;Vaessen et al 2006;Martinelli et al 2007;Maasz and Kisfali 2008a, b;Feitosa et al 2011), and a growing number of triglyceride modifying alleles are being identified (Ordovas et al 1991;Dallinga-Thie et al 1997; Baroni et al 2003;Talmud et al 2009). Some of them are associated with increased, while others with decreased triglyceride levels Baroni et al 2003;Izar et al 2003;Kathiresan and Melander 2008b;Kathiresan et al 2009); the analysis of their functional role in different diseases had already begun (Pedro-Botet et al 1992; Baroni et al 2003;Izar et al 2003;Frikke-Schmidt et al 2004;Ma et al 2004;Souverein et al 2005;Havasi et al 2006;Vaessen et al 2006;Freiberg et al 2008;Willer et al 2008;Kathiresan and Melander 2008a;Kathiresan et al 2009;Labreuche et al 2009;Perez-Martinez et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The role of APOA5 alleles had already been widely studied (Szalai et al 2004;Vaessen et al 2006;Martinelli et al 2007;Maasz and Kisfali 2008a, b;Feitosa et al 2011), and a growing number of triglyceride modifying alleles are being identified (Ordovas et al 1991;Dallinga-Thie et al 1997; Baroni et al 2003;Talmud et al 2009). Some of them are associated with increased, while others with decreased triglyceride levels Baroni et al 2003;Izar et al 2003;Kathiresan and Melander 2008b;Kathiresan et al 2009); the analysis of their functional role in different diseases had already begun (Pedro-Botet et al 1992; Baroni et al 2003;Izar et al 2003;Frikke-Schmidt et al 2004;Ma et al 2004;Souverein et al 2005;Havasi et al 2006;Vaessen et al 2006;Freiberg et al 2008;Willer et al 2008;Kathiresan and Melander 2008a;Kathiresan et al 2009;Labreuche et al 2009;Perez-Martinez et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…metabolic consequences, including triglyceride level increases, confirming risk for cardiovascular diseases, metabolic syndrome or for cerebrovascular diseases, especially stroke events [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The National Cholesterol Education Program (NCEP) in 2001 ascertained several markers which are in strong association with coronary risk, stratified as risk factors related to lifestyle, such as physical inactivity, obesity, atherogenic diet; and emerging risk factors, as lipoprotein profile, homocysteine level, changed fasting glycaemia and evidence of subclinical atherosclerosis.…”
mentioning
confidence: 99%
“…As a prominent example, the functional role of APOA5 polymorphisms had already been widely investigated [1][2][3][4][5][6][7]. Several of them are associated with elevated triglyceride levels and higher risks for ischemic stroke and cardio-or cerebrovascular diseases or for metabolic syndrome [4, 5, 8-11, 21, 22].…”
mentioning
confidence: 99%
“…The protocol was approved by the Institutional Review Boards of University of Minnesota, University of Utah, Tufts University/New England Medical Center, and the University of Alabama at Birmingham. More details about the GOLDN study have been published in earlier reports [17][18][25][26][27]. Baseline and postfenofibrate intervention data were available for 750 participants with DNA methylation measurements.…”
Section: Methodsmentioning
confidence: 99%